PSA molecular no estadiamento do câncer da próstata - Borba, Sebastião Antônio (2003)
A search for serum markers for prostate câncer detection and staging is the ultimate goal in clinicai diagnostic. Therefore, PSA mRNA leveis were investigated through nested RT- PCR in perifheral blood mononuclear cells of patients submitted to radical prostatectomy to evaluate its association to the TNM 92 histological staging and to the total PSA serum leveis in the post-surgery follow-up, in order to establish a molecular staging for the prostate câncer and avaliate the clinicai prognostic aiming the cure after surgery. Patients and methods: A group of patients with prostate câncer (PCa) consisted of 32 individuais that were subtnirted to radical prostatectomy with the following criteria: Gleason score lower than 8; total PSA (tPSA) serum leveis lower or equal to 20 ng/mL (IMMULITE®); negative bone mapping and X-rays image analysis for tPSA greater than 10 ng/mL; rectal examination compatible with organ conftned câncer; age limit up to 80 years old with a life expectancy of 10 years or more. PSA mRNA was also detected through nested RT-PCR in pre-surgery blood samples, and positivity was associated to the TNM 92 histological staging, and to the diagnostic of organ confined and extracapsular invasion or metastatic disease, based on total tPSA serum leveis measured after surgeiy. For the post-surgery follow-up, the tPSA cutoff limit of 0.04 ng/mL was used to separate the organ confined from extracapsular invasion or metastatic disease. The control group consisted of 14 patients with bemgn prostate hyperplasia (BPH) that were submitted to either transurethral resections or to open prostatectomies (trans-vesical or retro pubic) according to the following inclusion criteria: histopathological results of BPH; tPSA serum leveis pre-biopsies lower or equal to 20 ng/mL and age limit up to 80 years. RT-PCR was also realized in pre-surgery blood samples. Results: TNM 92 staging was accomplished based on the inclusion criteria, and 18 patients (56.3%) presented organ confined câncer (pTl and pT2) and 14 (43.7%) had a possible localABSTRACT invasion or a metastatic disease (pT3, pT4 and pNl). RT-PCR was positive in 3 of 6 BPFI patients (50%), in 6 of 11 organ confíned PCa patients (54.5%), and in 4 of 7 local invasion or metastatic PCa patients (57.1%). Considering only patients diagnosed with extracapsular câncer invasion or metastasis and BPH, the molecular detection had a sensitivity, specificity, positive and negative predictive values, and accuracy of 57%, 50%, 57%, 50% and 54%, respectively. From those patients with organ confíned disease, the post-surgery tPSA cutoff limit have detected extracapsular câncer invasion or metastasis in 38.9% (7 of 18) while for those patients with extracapsular câncer invasion or metastasis 15.4% (2 of 13) have presented laboratorial cure, with a final result of 58.1% of patients with extracapsular câncer invasion or metastasis. Within those patients with extracapsular câncer invasion or metastasis, 80% presented positive RT-PCR, and within the organ confíned câncer patients it was found a positivity of 14.3% (1 of 7), with a sensitivity, specifícity, positive and negative predictive values, and accuracy of 80%, 85.7%, 88.9%, 75% and 82.4%, respectively. Conclusions: The positive results of RT-PCR-PSA in pre-surgery blood samples presented an excellent association with extracapsular câncer invasion or metastasis, based on the cutoff limit of the post-surgery tPSA serum leveis. The high sensitivity, specifícity and accuracy of this molecular marker to detect extracapsular câncer invasion or metastasis in pre-surgery blood have improved signifícantly the clinicai prognostic, suggesting the use of RT-PCR-PSA as a methodology íor molecular staging.